ANALYSIS OF THE EFFECT OF FROST IN THE LAND COVER IN CANDIDO MOTA - SP, BRAZIL, BY MEANS OF VEGETATION INDICES - Demarchi, Julio Cesar [UNESP]; Piroli, Edson Luis [UNESP] (Univ Federal Goias, Inst Estudos Socio-ambientais, 2015)
Frosts affect negatively the agricultural production and, consequently, the society and economy by decreasing productivity and creasing in food prices. This paper aimed to analyze the effects of the frosts occurred on June 28th and on August 4th, 2011, in the city of Candido Mota, Sao Paulo state, by means of vegetation indices, such as Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI). Also, it verifies the influence of altitude in the intensity of this climatic phenomenon and their effects in vegetation cover and some agricultural crops, and evaluates the effectiveness of these indices in detecting changes caused by frosts in vegetation cover. The NDVI and NDWI difference images of previous and posterior dates to the first and the second frosts and the zonal analysis pointed out that the main affected crops were: winter corn, barley, wheat and sugarcane. The effect of the frosts was higher in medium altitudes (400 to 500 m). The indices NDVI and NDWI had similar performance in detecting the effect of frosts in vegetation cover, although they have been designed for different purposes.
Keywords: NDVI; NDWI; altitude; remote sensing